Sickness absence and works councils: Evidence from German individual and linked employer-employee data - Daniel Arnold; Tobias Brändle; Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2014)
Using both household and linked employer-employee data for Germany, we assess the effects of non-union representation in the form of works councils on (1) individual sickness absence rates and (2) a subjective measure of personnel problems due to sickness absence as perceived by a firm's management. We find that the existence of a works council is positively correlated with the incidence and the annual duration of absence. We observe a more pronounced correlation in western Germany which can also be interpreted causally. Further, personnel problems due to absence are more likely to occur in plants with a works council.
Keywords: J53; I18; M54; 330; absenteeism; LIAB; personnel problems; sickness absence; SOEP; works councils